Monovalent lanthanide(I) in borozene complexes - Wan-Lu Li (Nature Portfolio, 2021)
The most common oxidation state for lanthanides is +3. Here the authors use photoelectron spectroscopy and theoretical calculations to study half-sandwich complexes where a lanthanide center in the oxidation state +1 is bound to an aromatic wheel-like B8 2- ligand.